Coursebook-Based ISIS’ Propaganda: A Critical Discourse Analysis of Arabic History Texts in ISIS’ School Environments - Akhmad Saehudin; Hilman Ridha (Insaniyat : Journal of Islam and Humanities, 2022)
This research aims to investigate forms of propaganda spread by the Islamic State of Iraq and Syria (ISIS) as represented in an Arabic History Coursebook they prepare for ISIS’ school environments. It utilizes Critical Discourse Analysis (CDA) as its research method to examine and reveal values and ideologies behind choices of words, grammar, and text structures. Using an ISIS’ Arabic History Coursebook entitled Al-Tarikh: li al-Shaff al-Khamis al-Ibtida'i (published in 2016/1437H) as the data source, this research is primarily focused on the analysis of clauses and phrases which contain words of daulah and qital. The data were analysed utilizing functional linguistics and propaganda techniques as its analytical framework. Results of analyses show that as an organization ISIS fights for ideologies which underlie the idea of the Islamic State and spreads values of radicalism to its targeted communities. Propaganda techniques such as name calling, glittering generality, transfer, plain folk and bandwagon are found to be dominant in ISIS’ propaganda projects.